HUBUNGAN KUALITAS TIDUR DENGAN TINGKAT KECEMASAN PADA PASIEN TERPASANG INFUS DI RUANG RAWAT INAP INTERNE RSUD DR. ACHMAD MOCHTAR BUKITINGGI - Dia Resti Dewi Nanda Demur (LPPM UNIVERSITAS PERINTIS INDONESIA, 2018)
Abstract According to WHO (World Health Organization, 2010) each year is estimated about 20% - 50% adults reported a sleep disorder and about 17% suffered serious sleep disorders. The purpose of this study was to determine association of sleep quality towards anxiety level with IV Catheter Therapy in Medical Internal Ward General Hospital Dr Achmad Mochtar Bukittinggi 2018. This research using descriptive analytic approach with cross sectional design. Data were processed with Chi Square test. The sample in this research are 63 respondents. Tool data collection using questionnaires. The data analysis of univariate more than half are 30 respondents (47,6%) has a good sleep quality and 33 respondents (52,4%) have bad sleep quality, more than half are 30 respondents (47,6%) have mild anxiety level and 33 respondents (52,4%) have a moderate anxiety level. There is a correlation bivariate analysis the existence of sleep quality to the level of anxiety With IV Catheter Therapy In Medical Internal Ward General Hospital Dr Achmad Mochtar Bukittinggi the value of p = 0,000. It is suggested that this research for general hospital Dr Achmad Mochtar Bukittinggi able to improve the quality of patient sleep and the characteristics anxiety levels where can be used as a basis for interving and improving nurses knowledge. Keywords : Anxiety Level, Sleep Quality